Masa Depan Hubungan Turki dan Amerika Serikat - Firmanda Taufiq (Jurnal ICMES, 2018)
Throughout 2018, relations between Turkey and the United States seemed to deteriorate. The leaders of the two countries issued sharp diplomatic statements and the US even imposed economic sanctions on Turkey. This article aims to analyze how the future of relations between Turkey and the United States. Cooperation between the two has a long historical side after the Cold War. Relations between the two countries are based on various interests, both economic, political, military and security interests. The theory used in this study is the theory of national interest. The US has great interests in the Middle East and Turkey is the front-line ally in achieving those interests. However, there are many US foreign policies that ignore the Turkish concern and create tensions between the two countries. On the contrary, Turkey also has considerable economic interests, but the role of the government elite (in this case, President Erdogan) has a significant influence in the determination of Turkish foreign policy. The findings of this study, although it will go through complex challenges and processes, the US and Turkey will continue to maintain their relations.